Co-research with adults with Intellectual Disability: a systematic review - Di Lorito, Claudio; Bosco, Alessandro; Birt, Linda; Hassiotis, Angela (Wiley, 2017)
Background. Co-research with people with intellectual disability (ID) is a distinct form of patient and public involvement (PPI). This systematic review summarises published studies and protocols to report on the process of co-research in social and health care research. Method. Relevant studies were identified using electronic searches on ASSIA, PsycInfo and MedLine. Study quality was assessed and information relevant to the process of working with co-researchers was extracted and thematically analysed. Results. Thirteen studies were retrieved. Data are reported under three themes: 1) challenges of co-research; 2) facilitators of co-research; 3) benefits of co-research. Best practice is presented as a model of co-research. Content analysis on 12 research protocols identified four themes related to PPI. Conclusions. All stakeholders involved in co-research with people with ID can benefit, providing there is adequate infrastructure to accommodate and empower the co-researchers. Many current ID research projects still lack systematic involvement of PPI members.